Dimensions of Consumption Value of Green Repurchase Intention with Green Trust as an Intervening Variable - Firman; Alqadri Jamal (Universitas Negeri Padang, 2021)
This riset means to analyze how the influence of consumption value with its dimensions of functional value, social value, emotional value on green repurchase intention on Garnier products in the city of Padang with green trust as a mediating variable. The method used is quantitative. The population is all customers who have shopped or purchased Garnier products. The research sample was 280 respondents. This research was conducted using the smart PLS 3.0 software using the structural equation model (SEM) test. The results found that: (1) functional value has a significantt direct effect on greenn trust. (2) social valuee has a significant direct effect on green trust (3) emotional value has a significant direct effect on green trust. (4) green trust has a ssignificant direct effect on green repurchase intention (5) functional value has a significant direct effect on green repurchase intention (6) social value does not have a significant direct effect on green repurchase intention (7) emotional value has a significant direct effect on green repurchase intention (8) functional value has a significant effect on green repurchase intention with green trust as a mediating variable. (9) social value hass a significantt effect on green repurchase intention with green trust as a mediating variable. (10) emotional value has a significant effectt on green repurchase intention with green trustt as a mediating variable.